Implementation of Web-Based SECI Knowledge Management Model For Coastal Communities - Darmawan, Daddy; Kustandi, Cecep; Syah, Rahmat; Wasan, Aan (Universitas Negeri Semarang, 2021)
The marine industry is an important resource in human life. The demand for seafood continues to increase almost all over the world, but catches continue to decline. Therefore, there is a need for a fisherman knowledge management system. The system becomes a collection of processes that coordinate information, knowledge, and experience that run and work together, so that the fishing community has an integrated system in catch management. This study aims to model knowledge management about the sustainability of capture fisheries and document the knowledge of fishermen. This study uses a qualitative approach with the Achieve method which seeks to describe the following objects or subjects as they are to convey facts and information systematically. The survey locations were carried out in several areas in 6 coastal locations in East Nusa Tenggara Province. The results of the practice in the fishing community become the basis for content in media creation. With the program, it can be seen from the activeness of coastal communities in conveying information. The same understanding of the benefits of information systems in web-based programs follows the existing concepts, such as togetherness, participation grows through consensus and shared vision, ideals, hopes, goals, and needs. Second, extending from the bottom, participation is not forced from top to bottom or controlled by individuals or groups through power mechanisms. Participation grows based on the awareness and needs felt by the community.